Infant feeding patterns and risk of acute respiratory infections in Baghdad/Iraq (Italian Journal of Public Health, 2012)
Background: exclusive breastfeeding has been shown to protect infants from contracting various diseases. The aims of this study were: to examine the relationships between infant feeding patterns and the risk of Acute Respiratory Infections (ARI), and to assess the importance of some factors that can increase such risk.Methods: a case-control study was carried out during the period between February 1st 2005 - May 1st 2005. The study included 137 infants who were hospitalized in the Children Welfare Teaching Hospital for ARIs during the period of study (a case definition of acute lower respiratory infection as given by the WHO (1995) was used). The Control group included 157 healthy infants who were randomly selected from two primary health care centers of the AI-Karkh sector of Baghdad for immunization. The risk of various factors thought to be associated to ARI were studied, these being: non-modifiable (age, gender, birth order, parent education, crowded residence, family history of asthma and history of ARIs in household members in previous 2 weeks) and modifiable (short duration of breastfeeding, cigarette smoking in proximity to the infant, delayed immunization and malnutrition). Logistic regression was used to adjust for confounders and for calculating adjusted odds ratios.Results: formula fed infants had a 2.7 times higher risk (CI:1.6-4.68) for ARIs compared to breast fed infants. Infants who had undergone a short duration of breastfeeding (
Keywords: Breastfeeding; Respiratory infections